Dampak dari Media Sosial Terhadap Sosial-Budaya di Masyarakat - Gusti Dametriana Sihombing (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2025)
Social media is a tool that makes it easier for owners to communicate with each other without time, distance, place and at a cheaper cost. Use of social media Because advanced technology has become important for society, technology can be both beneficial and detrimental in society, especially in changes in the social culture of society itself. Social media has now become a part of people's lives, because modern society cannot live without mass media. With mass communication, social and cultural changes in society are very visible because after mass communication, as time goes by, norms, habits and attitudes slowly collapse and are increasingly forgotten in society and replaced by new ways. From year to year, technological developments are seen to be increasingly advanced, especially in promotion on social media, the impact of which the public must be aware of. The negative impacts of using social media do not reach people. In line with the development of information technology, the same thing also happens in community life. Information technology is the technology most widely used in society, namely social media. Various activities have become easier thanks to the presence of social media in our lives. But the fact is that now there are more people than the surrounding environment on busy social media. Now you can They say we live in the digital era. In this digital era, the world is very much in our hands. Even though we are only in one place at one time, we can monitor the situation anywhere in the world, we are even connected through social media with everyone. Social media has become an alternative means of communication for society to shorten distance and time. Socio-cultural changes are symptoms of changes in socio-cultural structures and models in society. Socio-cultural change is a common phenomenon that always occurs in every society. These changes occur as they should. The nature and essence of people who always want to make changes. Some say that societal boredom is actually the cause of change.